2008
DOI: 10.1073/pnas.0808763105
|View full text |Cite
|
Sign up to set email alerts
|

HCO 3 /Cl anion exchanger SLC4A2 is required for proper osteoclast differentiation and function

Abstract: As the only cell capable of bone resorption, the osteoclast is a central mediator of skeletal homeostasis and disease. To efficiently degrade mineralized tissue, these multinucleated giant cells secrete acid into a resorption lacuna formed between their apical membrane and the bone surface. For each proton pumped into this extracellular compartment, one bicarbonate ion remains in the cytoplasm. To prevent alkalinization of the cytoplasm, a basolateral bicarbonate/chloride exchanger provides egress for intracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
86
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(90 citation statements)
references
References 35 publications
2
86
0
Order By: Relevance
“…This latter protein is a critical mediator of both osteoclast differentiation and function, where Slc4a2 -/-osteoclasts are unable to resorb mineralized tissue and fail to express TRAP activity (Wu et al, 2008). Taken together, these microarray findings suggested that osteoclast activity and/or bone turnover may be increased in the bgn mice.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…This latter protein is a critical mediator of both osteoclast differentiation and function, where Slc4a2 -/-osteoclasts are unable to resorb mineralized tissue and fail to express TRAP activity (Wu et al, 2008). Taken together, these microarray findings suggested that osteoclast activity and/or bone turnover may be increased in the bgn mice.…”
Section: Discussionmentioning
confidence: 82%
“…fmod -/-samples that are related to osteoclast function/differentiation and bone turnover, including CART prepropeptide (Elefteriou et al, 2005), secreted frizzled-related sequence protein 1 (Hausler et al, 2004), arylsulfatase K (Baron et al, 1990), solute carrier family 4, member 1 (Wu et al, 2008), and protein tyrosine phosphatase, receptor type V (Lee et al, 2007). More specifically, CART prepropeptide inhibits bone resorption by modulating RANKL expression (Elefteriou et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For Von Kossa staining of extracellular matrix mineralization, cells were fixed with 10% neutral formalin buffer and stained with 2.5% silver nitrate (Sigma-Aldrich). Analysis of osteoclast differentiation and TRAP staining was performed as previously described (45). Serum CTX was measured using the Rat Laps EIA Kit (Immunodiagnostiosystems).…”
Section: Methodsmentioning
confidence: 99%
“…Fzd1 is an antagonist of canonical Wnt/beta-catenin signaling (17), and this signaling pathway plays an important role during tooth development (18,19). SLC4a2 is required for osteoclast differentiation and function (20). It is known that SHH and the SHH signaling pathway play an important role during tooth development (21,22).…”
Section: Methodsmentioning
confidence: 99%